Sexual Orientation Affects Neural Responses to Subtle Social Aggression Signals. - Lübke, Katrin T.; Storch, Dunja; Pause, Bettina M. (Archives of Sexual Behavior, 2024)
The current series of studies are the first to examine brain responses to social aggression signals as a function of male and female sexual orientation. For the first set of studies (1a, 1b), axillary sweat had been collected from 17 heterosexual men and 17 heterosexual women aggressively responding to frustrating opponents (aggression condition) and while playing a construction game (control condition). Sweat samples were pooled according to sex and condition, and presented via a constant flow olfactometer to 17 gay and 23 heterosexual men (Study 1a), and 19 lesbian and 25 heterosexual women (Study 1b). Ongoing EEG was recorded from 61 scalp locations, chemosensory event-related potentials (CSERPs; P2, P3-1, P3-2) were analyzed, and neuronal sources calculated (low resolution electromagnetic tomography). Within the second set of studies (2a, 2b), pictures of males' and females' weak angry and neutral facial expressions were presented to 21 gay and 23 heterosexual men (Study 2a), and 19 lesbian and 26 heterosexual women (Study 2b), and ERPs (N170, P3) were analyzed. Gay men showed larger P3-1 amplitudes than heterosexual men upon presentation of male aggression sweat, accompanied by activation of the right inferior frontal gyrus (IFG, BA 10). Gay men also displayed longer N170 latencies in response to men's compared to women's angry facial expressions, while heterosexual men did not. In women, sexual orientation did not affect the processing of aggression sweat or anger expressions. Gay men showed preferential processing of chemosensory aggression signals (P3-1 amplitudes), indicating fine-tuned socioemotional sensitivity, related to activation of brain areas involved in emotion regulation (IFG). They further process the relative relevance of visual aggression signals (N170 latency). These results were in line with theories proposing a common evolutionary pathway for same-sex attraction and traits easing social integration.